Geographic strain differentiation of Schistosoma japonicum in the Philippines using microsatellite markers. - Kharleezelle J Moendeg; Jose Ma M Angeles; Ryo Nakao; Lydia R Leonardo; Ian Kendrich C Fontanilla; Yasuyuki Goto; Masashi Kirinoki; Elena A Villacorte; Pilarita T Rivera; Noboru Inoue; Yuichi Chigusa; Shin-Ichiro Kawazu (Public Library of Science (PLoS), 2017)
Microsatellites have been found to be useful in determining genetic diversities of various medically-important parasites which can be used as basis for an effective disease management and control program. In Asia and Africa, the identification of different geographical strains of Schistosoma japonicum, S. haematobium and S. mansoni as determined through microsatellites could pave the way for a better understanding of the transmission epidemiology of the parasite. Thus, the present study aims to apply microsatellite markers in analyzing the populations of S. japonicum from different endemic areas in the Philippines for possible strain differentiation.Experimental mice were infected using the cercariae of S. japonicum collected from infected Oncomelania hupensis quadrasi snails in seven endemic municipalities. Adult worms were harvested from infected mice after 45 days of infection and their DNA analyzed against ten previously characterized microsatellite loci. High genetic diversity was observed in areas with high endemicity. The degree of genetic differentiation of the parasite population between endemic areas varies. Geographical separation was considered as one of the factors accounting for the observed difference between populations. Two subgroups have been observed in one of the study sites, suggesting that co-infection with several genotypes of the parasite might be present in the population. Clustering analysis showed no particular spatial structuring between parasite populations from different endemic areas. This result could possibly suggest varying degrees of effects of the ongoing control programs and the existing gene flow in the populations, which might be attributed to migration and active movement of infected hosts from one endemic area to another.Based on the results of the study, it is reasonable to conclude that genetic diversity could be one possible criterion to assess the infection status in highly endemic areas. Genetic surveillance using microsatellites is therefore important to predict the ongoing gene flow and degree of genetic diversity, which indirectly reflects the success of the control program in schistosomiasis-endemic areas.